Plant lipid phosphate phosphatases: current advances and future outlooks. (3rd April 2023) - Su, Wei; Raza, Ali; Gao, Ang; Zeng, Liu; Lv, Yan; Ding, Xiaoyu; Cheng, Yong; Zou, Xiling
Abstract: Lipids are widely distributed in various tissues of an organism, mainly in plant storage organs (e.g., fruits, seeds, etc.). Lipids are vital biological substances that are involved in: signal transduction, membrane biogenesis, energy storage, and the formation of transmembrane fat-soluble substances. Some lipids and related lipid derivatives could be changed in their: content, location, or physiological activity by the external environment, such as biotic or abiotic stresses. Lipid phosphate phosphatases (LPPs) play important roles in regulating intermediary lipid metabolism and cellular signal response. LPPs can dephosphorylate lipid phosphates containing phosphate monolipid bonds such as: phosphatidic acid, lysophosphatidic acid (LPA), and diacylglycerol pyrophosphate, etc. These processes can change the contents of some important lipid signal mediation such as diacylglycerol and LPA, affecting lipid signal transmission. Here, we summarize the research progress of LPPs in plants, emphasizing the structural and biochemical characteristics of LPPs and their role in spatio-temporal regulation. In the future, more in-depth studies are required to boost our understanding of the key role of plant LPPs and lipid metabolism in: signal regulation, stress tolerance pathway, and plant growth and development.